Prognostic factors of clot resolution on follow‐up computed tomography angiography and recurrence after a first acute pulmonary embolism. (27th May 2021) - Aranda, Carlos; Gonzalez, Paula; Gagliardi, Lidia; Peralta, Luisa; Jimenez, Angel
Abstract: Background: Recent studies seem to confirm the relationship between residual pulmonary obstruction (RPO) in pulmonary embolism (PE) and risk of recurrent thrombosis and chronic thromboembolic pulmonary hypertension (CTEPH). However, the prognostic factors associated with PE resolution on follow‐up computed tomography angiography (CTA) are not clear. Objectives: To determine the prognostic factors of resolution of PE diagnosed and monitored by CTA and the impact of RPO on late complications. Methods: We retrospectively analyzed 241 patients with PE who had undergone a 12‐month follow‐up and CT scan evaluation at 6 months. Factors related to resolution and the impact of RPO on the outcome were analyzed. Results: Resolution was achieved in 74.3% of all cases after 6 months of treatment. Absence of chronic obstructive pulmonary disease (COPD) (OR, 3.22 [1.35–7.71]; p  = 0.009), provoked PE (OR, 2.02 [1.08–3.79]; p  = 0.028), early initiation of treatment (<7 days) (OR, 2.42 [1.22–4.78]; p  = 0.011), and degree of obstruction caused by the initial PE as indicated by a Qanadli score lower than 16 (OR, 2.12 [1.03–4.37]; p  = 0.043) were associated with complete resolution. RPO was associated with recurrent PE as well as the combined endpoint consisting of recurrent VTE and/or CTEPH (4.67 [95% CI, 1.26–17.26]; p  = 0.02) and (OR 6.4 [95% CI, 1.9–21.2]; p  < 0.005), respectively. Conclusions: Resolution of PE is associated with a lower risk of recurrent thrombosis. Earlier initiation of treatment improves prognosis as measured by resolution on follow‐up CTA.